Clinical and pathological features of Kaposi sarcoma herpesvirus-associated inflammatory cytokine syndrome. (15th November 2020) - Piñeiro, Florencia; Climent, Fina; Imaz, Arkaitz; Gudiol, Carlota; Niubó, Jordi; Palomar-Muñoz, Azahara; Serrano, Teresa; Saumoy, Maria; Podzamczer, Daniel
Abstract : N/A: Kaposi sarcoma Herpesvirus (KSHV)-associated inflammatory cytokine syndrome (KICS) is an uncommon but aggressive human Kaposi sarcoma herpesvirus associated disorder that is mostly reported in people living with HIV. The diagnosis of KICS is based on clinical criteria, and, in contrast to other KSHV-related malignancies, characteristic pathological features have not yet been described. We report novel clinical and pathological features in an HIV-1 infected patient diagnosed with KICS. Abstract : Supplemental Digital Content is available in the text